Phyllodes Tumor on Male Breast: A Literature Review - Dzulhijar, Naufal; Yamsun, Muhammad (Indonesian Journal of Cancer, 2024)
Background: Phyllodes tumor is a neoplasm from the fibroepithelial lesion and is rare to be found. Hence, there are some case reports that phyllodes tumor also can be found in the male breast. From 1990 until 2020, 13 articles show the phyllodes tumor in the male breast. The incidence of this tumor is 6.92% of all malignancies in the breast and occurs at a younger age, ie 25-30 years. Despite the rare cases of phyllodes tumors on male breasts, this study aims to explore and summarize the risk factors, diagnostic approaches, and treatment used for the cases. Methods: This literature review is synthesized with analysis of the source of information from online databases, such as NCBI, Google Scholar, Science Direct, Elsevier, Springer Nature, Wiley Online Library, World Health Organization, Kementerian Kesehatan Republik Indonesia, and Perhimpunan Onkologi Indonesia (POI). The keywords are “phyllodes tumor on male breast” and “tumor filodes pada pria”. Thirteen articles provided the cases by years of publication later than 2012, but only 7 cases fulfilling inclusion and exclusion criteria were used for analysis. Results: Phyllodes tumors on the male breast would likely appear in those who have gynecomastia or prostate disease and are currently on therapy for the disease. Gynecomastia has the potential to affect an estrogen/androgen imbalance. Several case studies mention that there is an incidence of breast tumors in men who use long-term estrogen therapy. Treatment with bicalutamide for men with prostate cancer can also lead to malignant phyllodes tumors in men. Conclusions: Phyllodes tumors on male breasts are rare cases that need to be understood by physicians for diagnostic approach and effective treatment. The male who have a history of gynecomastia or prostate disease should be cautious as they can develop phyllodes tumors in the future.